The Relationship Between Mastery of Hard Skill and Job Readiness of Grade XI Students at SMK Islam Al-Fajar Kedaung Pamulang South Tangerang - Indri Apriyani; Metha Lubis (International Journal of Economics Education Research (IJEER), 2024)
The objective of this study is to determine the significant relationship between hard skill mastery and job readiness among Grade XI students at SMK Islam Al-Fajar. This research employs a quantitative approach with an associative method, involving a population of 102 Grade XI students and a randomly selected sample of 81 individuals. Data collection techniques include observation, interviews, questionnaires, and documentation. The hypothesis test was conducted using a correlation test. The results of the study indicate that there is a relationship between hard skill mastery and job readiness. The significance value (Sig.) for variable X (hard skill mastery) is 0.000, as is the value for variable Y (job readiness), 0.000, indicating that these two variables are correlated. The nature of the relationship between the two variables is positive with a very strong correlation level, evidenced by a value of 0.754.